Majmaʻ al-baḥrayn / Dārā Shikoh ; muʾallafah Muḥammad Yūnus Shāh Gīlānī. - Dārā Shikūh, Prince, son of Shahjahan, Emperor of India, 1615-1659. (al-Gilān Pablisharz, 1983)
On Sufism; includes author's biography by the translator.